(untitled) (Global Journal of Management and Business Research, 2023)
The main objective of this research is to investigate the consumer satisfaction in the context of booming fast-food industry of Cameroon. More precisely, we break the satisfaction concept into different constructs, atmosphere satisfaction, menu satisfaction and global satisfaction, based on the different drivers of satisfactions; we then evaluate the influence of atmosphere satisfaction and menu satisfaction on global satisfaction as well as the impact of the three dimensions of satisfaction on consumers loyalty. The researcher also evaluated the moderator role of global satisfaction on the relationship linking atmosphere and menu satisfaction to loyalty. The study results indicated that fast-food menu and the atmosphere satisfaction have a positive effect on global satisfaction. As well, out of the three dimensions of satisfaction, global and menu satisfaction proved to have a positive impact on consumer loyalty, but effect of the atmosphere satisfaction proves to be not determinant. In addition, the mediator role of global satisfaction proved to be relevant.